Spatial Pattern and Key Environmental Determinants of Vegetation in Sand Mining and Non-Mining Sites along the Panjkora River Basin - Kishwar Ali (14581226) (2022)
A specific set of environmental conditions characterizes plant species patterns and distribution on Earth. Similarly, riparian vegetation can be impacted by anthropogenic activities like mining practices involving the removal of vegetation cover, which destroys the structure and diversity of the habitat, adversely affecting the ecosystem services. In this study, we explored the role of environmental variables and biotic intervention in deriving spatial patterns and distribution of riparian vegetation at mining and non-mining sites along the most depleted Panjkora River basin in NW Pakistan. Vegetation data and its determining factors at 28 mining and non-mining sites (14 each) were sampled using 10 m × 10 m (100 m2) systematic plots at 50 m intervals along transects in a downstream direction from the upper catchments to the bottom junction with the Swat River. We recorded 186 species in both mining and non-mining sites, belonging to 70 families comprising 174 angiosperms, 3 gymnosperms, and 9 Pteridophytes. Results show that annual or perennial therophytic life forms predominated in the Panjkora River system, indicating anthropogenic disturbances. At the same time, the aggressively invasive species, such as Xanthium strumarium and Cannabis sativa, further heightened plant community disturbances. Generally, the species diversity was higher in non-mining sites and may be attributed to habitat fragmentation. Likewise, the Canonical Correspondence Analysis (CCA-ordination) revealed that geographic coordinate (i.e., latitude r = 0.80; longitude r = 0.75) and elevation (r = 0.95) were more meaningful predictors than soil texture (i.e., silt%, r = −0.30), nutrients (i.e., potassium, r = −0.35; phosphorus, r = 0.38) and soil pH (r = −0.50) in shaping the spatial pattern and vegetation structure. Our result implies that the present vegetation composition and spatial assemblages are due to heavy anthropogenic interventions, especially mining activities. Therefore, the heavily degraded fragile riparian system of the Panjkora River and its tributaries needed to be conserved and restored by predicting the composition of communities in response to changing climatic conditions. Other Information Published in: Land License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/land11101801 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.